2013
DOI: 10.1017/s0960129513000182
|View full text |Cite
|
Sign up to set email alerts
|

Computability structures, simulations and realizability

Abstract: We generalize the standard construction of realizability models (specifically, of categories of assemblies) to a wide class of computability structures, broad enough to embrace models of computation such as labelled transition systems and process algebras. We consider a general notion of simulation between such computability structures, and show how these simulations correspond precisely to certain functors between the realizability models. Furthermore, we show that our class of computability structures has go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Related to the work of Boker and Dershowitz, is that of Cockett and Hofstra [9], and Longley [26] which are both concerned with category-theoretic descriptions of abstract computational models. In these frameworks model equivalence is interpreted by categorical isomorphism, and so akin to the strongest notion of equivalence considered by Boker and Dershowitz.…”
Section: Expressiveness Of Factorisation: Discussion and Related Workmentioning
confidence: 99%
“…Related to the work of Boker and Dershowitz, is that of Cockett and Hofstra [9], and Longley [26] which are both concerned with category-theoretic descriptions of abstract computational models. In these frameworks model equivalence is interpreted by categorical isomorphism, and so akin to the strongest notion of equivalence considered by Boker and Dershowitz.…”
Section: Expressiveness Of Factorisation: Discussion and Related Workmentioning
confidence: 99%
“…This notion is rooted in previous work of Longley in[6][7][8], and is influenced by the work of Cockett and Hofstra in[3] and[4] (see[9], p. 52).…”
mentioning
confidence: 89%
“…Longley and Normann associated in a canonical way to a computability model 2 C its category of assemblies Asm(C), "the world of all datatypes that can be represented in" C. They also showed that the computability models C and D are equivalent if and only if the categories of assemblies Asm(C) and Asm(D) are equivalent. The category of computability models and the corresponding functor C → Asm(C) are studied extensively in [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second reason for moving to this level of generality is a potential connection with more general forms of realizability. Longley has recently proposed a notion of 'computability structure' [Lon13] that encompasses partial combinatory algebras and is similar to the 'basic combinatorial objects' of Hofstra [Hof06]. Each of these is clearly trying very hard to be a category enriched in some sort of 2-category, and so one might wonder whether they are examples of a still more general notion of 'coefficient object' for realizability that encompasses the two, and whether the passage from a partial combinatory algebra to its associated tripos can be seen in the context of the equivalence between fibrations and categories enriched in certain 2-categories.…”
Section: 'Variation Through Enrichment'mentioning
confidence: 99%